2005
DOI: 10.1029/2005jc002881
|View full text |Cite
|
Sign up to set email alerts
|

Ocean wave directional spectra estimation from an HF ocean radar with a single antenna array: Observation

Abstract: [1] A method of estimating ocean wave directional spectra using a]high-frequency (HF) radar with a single antenna array was applied to actual ocean data. This method incorporates the wave energy balance equation and the continuity equation of wind vectors into the inversion method to solve the integral equation which relates a Doppler spectrum to wave spectra. This method uses dynamic extrapolation to estimate wave spectra at positions where the signal-to-noise (SN) ratio in Doppler spectra is not high. The ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“… Wyatt et al [1999] demonstrated that such dual‐site inversion methods can obtain reliable wave spectral estimates when compared with moored buoys. Hisaki [2005] has produced wave spectral estimates using a blend of single site radar observations and a wave model. This hybrid approach is likely to be quite useful for extending the range of HF wave observations, but is of limited use for focused wave studies because the wave field has been assumed to take a specified form.…”
Section: Methodsmentioning
confidence: 99%
“… Wyatt et al [1999] demonstrated that such dual‐site inversion methods can obtain reliable wave spectral estimates when compared with moored buoys. Hisaki [2005] has produced wave spectral estimates using a blend of single site radar observations and a wave model. This hybrid approach is likely to be quite useful for extending the range of HF wave observations, but is of limited use for focused wave studies because the wave field has been assumed to take a specified form.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, these factors all deserve more study. Another challenging problem is how to inverse the directional wave spectra from the second-order radar echoes, which can give more information of ocean waves than significant waveheight, as what had been done by some other authors [8][9][10][11][12] . The study is under progress now.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, the significant waveheight can be derived from the integral of the secondorder echo spectra. In the following years, Lipa et al [8] , Wyatt [9] , Howell et al [10] , Hisaki [11] and Green et al [12] proposed several methods to obtain directional wave spectrum through the inversion of Barrick's second-order nonlinear equation. All methods would provide more comprehensive information on directional wave spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments we did not consider all types of data available for regional modeling. In particular, directional spectra (with a coarser resolution and larger uncertainties) can be obtained from high-frequency radars (Graber and Heron 1997;Hisaki 2005) and spaceborne (Tison et al 2008;Ren et al 2010) platforms. Simplifying assumptions have been also made in configuring WAM: the background currents (;0.2-0.4 m s 21 ) were assumed to be negligible in comparison with the wave velocities (;5-10 m s 21 ) of the major spectral peak and stationary conditions at the open boundaries were specified due to relatively short period of model integration.…”
Section: Conclusion and Discussionmentioning
confidence: 99%